Democracy fatigue. - FREELAND, CHRYSTIA (Prospect, 2014)
The article offers information on the fight for democracy in Ukraine which is being trounced by the West in their geopolitical war with Russia. Topics discussed include Euromaidan protests in Kiev, Ukraine, political and geopolitical importance of Ukraine, and authoritarian rule of Russian President Vladimir Putin.